PERSEPSI MAHASISWA UNTIRTA TERHADAP PENERAPA PERDA SYARIAH DI KOTA SERANG: Hadi Suprapto Arifin, Engkus Kuswarno, Benyamin Pramono - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2017)
Regional autonomy has been giving a very strong impetus for the regions to regulate the area in accordance with the aspirations of the people in the area. Various products come as a form of public kebiajakan otomoni area. Implementation and the existence of Sharia regulations in Serang has some pros and cons in the community. The purpose of this study was to describe the perceptions of students Untirta on the application of sharia regulations in the town of attack. Design of this study is to approach kunatitatif survey method. The data analysis in this study is the descriptive statistical analysis. Results of analysis show that the general perception is very good student of the existence of Sharia regulations were implemented in the city of Serang. It can be seen from the general student perceptions of the existence and application of sharia regulations in the City attack is quite good. For 73.5 percent of the students assess the existence and application of sharia regulations quite well and according to the needs and conditions of people in Serang, while students assess sharia regulations are less precise and less well by only 23.0 percent.